MAVEN observations of solar wind hydrogen deposition in the atmosphere of Mars. Issue 21 (5th November 2015) - Halekas, J. S.; Lillis, R. J.; Mitchell, D. L.; Cravens, T. E.; Mazelle, C.; Connerney, J. E. P.; Espley, J. R.; Mahaffy, P. R.; Benna, M.; Jakosky, B. M.; Luhmann, J. G.; McFadden, J. P.; et al.
Abstract: Mars Atmosphere and Volatile EvolutioN mission (MAVEN) observes a tenuous but ubiquitous flux of protons with the same energy as the solar wind in the Martian atmosphere. During high flux intervals, we observe a corresponding negative hydrogen population. The correlation between penetrating and solar wind fluxes, the constant energy, and the lack of a corresponding charged population at intermediate altitudes implicate products of hydrogen energetic neutral atoms from charge exchange between the upstream solar wind and the exosphere. These atoms, previously observed in neutral form, penetrate the magnetosphere unaffected by electromagnetic fields (retaining the solar wind velocity), and some fraction reconvert to charged form through collisions with the atmosphere. MAVEN characterizes the energy and angular distributions of both penetrating and backscattered particles, potentially providing information about the solar wind, the hydrogen corona, and collisional interactions in the atmosphere. The accretion of solar wind hydrogen may provide an important source term to the Martian atmosphere over the planet's history. Key Points: We observe H + and H − in the atmosphere of Mars, at the solar wind energy Solar wind protons charge exchange and penetrate as ENAs then reconvert MAVEN can monitor hydrogen deposition and backscatter in the atmosphere